MODEL DEVELOPMENT VILLAGES TO ENHANCE QUALITY OF LIFE BY THE PHILOSOPHY OF SUFFICIENCY ECONOMIC - Dhirabhaddo, Phramaha Nuntawit; Klaythanee, Suphangpim (Journal of Buddhist Anthropology, 2020)
This research is a qualitative research. By studying documents, publications, online media, and interviewing experts who are knowledgeable about the sufficiency economy philosophy. With 3 objectives which are 1) to study the concepts of the sufficiency economy philosophy, the model village to enhance the quality of life according to the sufficiency economy philosophy 2) to study the methods of the development of the model to enhance the quality of life according to the economic philosophy 3) to present the model of village development to enhance the quality of life according to the sufficiency economy philosophy From the research, it was found that Khlong Jek Risk Village Phichit Province Is a model village that can enhance good quality of life in accordance with the philosophy of sufficiency economy For interested communities From the study of how to develop a model to enhance good quality of life in accordance with the sufficiency economy philosophy The village has applied the philosophy of sufficiency economy in the medium of Buddhism. By adopting the model development methods to enhance the quality of life according to the sufficiency economy philosophy as follows: moderation, reasoning, and having good immunity in oneself And develop it for a model village such as organic agriculture Farming with natural methods, etc., makes the village people in harmony. And save on living expenses by using the sufficiency economy concept To live by the 3 principles of the middle way moderately, reasonably, have good immunity in yourself And living with 2 conditions according to the sufficiency economy In terms of knowledge Moral conditions And the Sufficiency Economy Philosophy of Buddhism Dhamma Method in the middle, with 8 elements. The result of this research is a new knowledge. To be used effectively "Model for the development of a model village to enhance good quality of life in accordance with the sufficiency economy philosophy"